Pengaruh Jarak Lintasan Terhadap Biaya Operasional Kapal Penyeberangan - Syamsul Asri; Misliah Idrus; Harlian Kustiwansa (Departemen Teknik Kelautan Universitas Hasanuddin, 2023)
Ship placement along a ferry route is commonly not similar according to tonnage and cargo capacity, such as what happened on the ferry route between Bira and Pamatata in South Sulawesi. The Bira-Pamatata ferry route is operated by three ferries, each with a different load capacity and tonnage of KMP Balibo 540 GT, KMP Kormomolin 884 GT, and KMP Bontoharu 1053 GT. Variations in load capacity and ship operating costs will undoubtedly affect the income disparities between ferry operators. The length of the distance of the ferry route and the number of frequencies also have an impact on how much a ship costs to operate. The purpose of this research is to establish how the length of the distance of the ferry route and ship frequency affected the operational cost for the ship of different sized. The benefit of this research is can be applied to estimate the optimum ship size regarding operational cost for a particular trajectory distance and frequency. The analysis's results establish that ship operational costs are influenced by distance. The cost of operating will rise linearly as the length of the distance of the ferry route increases. There is a rise in operational cost (Rp/SUP) for variations in distance of Rp.262.40 for KMP Balibo, Rp.213.13 for KMP Kormomolin, and Rp.234.49 for KMP Bontoharu for each 1-mile added. The ship's operating time is affected by distance as well. The frequency that can be reached by ship decreases as the distance gets lengthy because the operating time of the ship also gets longer. Operational cost (Rp/SUP) for variations in frequency tends to decrease exponentially as a result of decreasing fixed costs. The analysis's results establish the operational cost (Rp/SUP) for the three cheapest distance and frequency variations sequential by KMP Balibo 540 GT, KMP Kormomolin 884 GT, and KMP Bontoharu 1053 GT for the 87-mile below. When the distance is 87 miles above, the graphic lines between KMP Kormomolin and KMP Bontoharu intersect at specific frequency variations, resulting in lower operational costs (Rp/SUP) for KMP Kormomolin than KMP Bontoharu.